Genetic and environmental components of female depression as a function of the severity of the disorder. Issue 10 (12th August 2016) - Rusby, James S. M.; Tasker, Fiona; Cherkas, Lynn
Abstract: Background: Both clinical care and genome‐wide studies need to account for levels of severity in the etiology of depression. The purpose of the study is to estimate the genetic and environmental components of female depression as a function of the severity of the disorder. Methods: A genetic and environmental model analysis of depression incidence was made using the IOP Depression Severity Measure (IDSM). Details of lifetime depression incidence were obtained by questionnaire from twins on the DTR registry. Data from 1449 matched female twin pairs in the age range 19–85 years in four ordinal categories of increasing severity were employed in the analysis. Results: Estimates of additive and dominance genetic components of 27% and 25% were found when all three levels of depression were included, and near zero and 33% when the recurrent/severe level was excluded. Shared environmental effects were not significant in either case, but the estimate for random environmental effects was greater when the severe level was excluded. Conclusions: These results suggest that the incidence of severe depression is associated with homozygotic alleles and the less severe with heterozygotic alleles. This is in accord with the finding that the hereditary component of severe depression is relatively high and that milder forms are more dependent on life‐time environmental factors. Such conclusions have clinical implications for the diagnosis and treatment of the disorder by practicing psychiatrists. They also lead to the importance of focusing future genome‐wide and linkage studies on those females with severe levels of depression if progress in identifying genetic risk loci is to be made. Abstract : The aim of the study was to estimate the genetic and environmental components of female depression as a function of the severity of the disorder using twin pair model analysis. It was found that the most severe level of depression had a significant additive genetic component and that the more moderate forms had a larger environmental component plus a modest dominant component. The corollary of this is that severe, or recurrent, depression is homozygotic and so more heritable.